2018
DOI: 10.1080/08830185.2018.1469629
|View full text |Cite
|
Sign up to set email alerts
|

IRF5-mediated immune responses and its implications in immunological disorders

Abstract: Transcription factors are gene regulators that activate or repress target genes. One family of the transcription factors that have been extensively studied for their crucial role in regulating gene network in the immune system is the interferon regulatory factors (IRFs). IRFs possess a novel turn-helix turn motif that recognizes a specific DNA consensus found in the promoters of many genes that are involved in immune responses. IRF5, a member of IRFs has recently gained much attention for its role in regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 140 publications
1
25
1
Order By: Relevance
“…13 It senses danger signals and induces inflammatory gene expression, giving rise to M1 macrophages. 10 The silencing or a deficiency of Irf5 hampers M1 macrophage polarization, 1 and in our study, we also confirmed that the myeloid-specific ablation of Irf5 reduces M1 macrophage polarization in the intestines of mice affected by NEC.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…13 It senses danger signals and induces inflammatory gene expression, giving rise to M1 macrophages. 10 The silencing or a deficiency of Irf5 hampers M1 macrophage polarization, 1 and in our study, we also confirmed that the myeloid-specific ablation of Irf5 reduces M1 macrophage polarization in the intestines of mice affected by NEC.…”
Section: Discussionsupporting
confidence: 83%
“…35,36 Upon the activation of TLRs by various stimuli, IRF5 participates in promoting downstream pro-inflammatory signaling. 10 Considering the important role of TLRs in NEC, 37,38 it is reasonable that IRF5 may also be induced in NEC. Indeed, our data show that IRF5 is upregulated in NEC and, more importantly, that it is mainly induced in infiltrated macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it was previously revealed that the IRF5 gene silencing suppressed levels of IRF5 in cardiac macrophages, reprogrammed their phenotype and supported the inflammatory resolution [58]. There are also some known IRF5 inhibitors [59], like TRIM28 or KAP1 [60], flavonoids called Baicalin (which simultaneously promotes M2 phenotype by IRF4 upregulation) [61] and Quercetin [62] or polyphenol called Mangiferin [63].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data from several studies has shown that IRF5 is a critical mediator in developing Th1 responses associated with the pathogenesis of various diseases, including autoimmune, metabolic, and infectious diseases [43] . Conversely, studies have also demonstrated that IRF5 plays a role in inducing Th2 responses [44,45] .…”
Section: Interferon Regulatory Factors (Irfs) Familymentioning
confidence: 99%